PENGGUNAAN MEDIA GAMIFIKASI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Ridwan Rudiyanto Kajah Kore; Imelda Voni Mone; Indriani Maria; Nanra Rosalina Nabu; Cindy Tamelab; Via Roliana Sodakain (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The decline in learning motivation among elementary school students is a significant concern in education. Many students feel bored and disengaged with conventional teaching methods. This study aims to examine the effect of gamification media on students' learning motivation. The research used a classroom action research method with two cycles, involving observation and motivation questionnaires. The results showed a significant increase in learning motivation scores after the application of gamification-based media such as interactive quizzes and point systems. The use of gamification effectively increased students' active participation, enthusiasm, and focus during learning activities. Gamified learning environments also promote a more dynamic and interactive atmosphere, encouraging curiosity and sustained attention, wcich are crucial in early education. These findings indicate that gamification media can serve as an effective learning strategy to enhance student motivation. Moreover, gamification tools are capable of accommodating various learning styles-visual, auditory, and kinesthetic-making the classroom experience more inclusive. The results are expected to be a reference for teachers in developing more engaging and enjoyable learning experiences in elementary classrooms. In this way, the integration of game-based elements has the potential to transform traditional instruction into a more student-centered and motivating process.